IMPACT OF INTERNAL AUDIT EFFECTIVENESS IN IMPROVING THE COMPANY'S PERFORMANCE (World Bulletin of Management and Law, 2022)
The study examines how internal audit improves industrial company performance. A questionnaire was created to assess internal audit effectiveness and firm performance improvement. (55) forms were distributed to the Chairman and members of the Board The study reached several results, including: internal audit contributes to improving the company's performance by activating its internal control systems by providing all the means and procedures used in the company to protect its assets from all types of losses. Internal audit contributes to supporting corporate governance through the relationship between internal audit and senior management, such as coordinating activities and communicating information, in addition to providing the necessary advisory services and suggestions. The study recommended working on the establishment of an internal audit committee in the company to activate this function, conducting continuous audit of all financial and non-financial operations without focussing only on financial aspects..